Cardiac autonomic imbalance in an overtrained athlete - Hederlin, R.; Wiklund, U.; Bjerle, P.; Henriksson-Larsen, K. (Medicine & Science in Sports & Exercise, 2000)
Purpose: In order to investigate overtraining-related adaptations in the autonomic nervous system, cardiac autonomic activity was examined in a junior cross-country skier who presented with reduced performance in competitions, early breathlessness during training sessions, and accumulated central fatigue. Methods: Power spectral analysis of heart rate variability (HRV) was performed before, when overtrained (OT), and after recovery (Rec). Results: In the overtrained state, high frequency (HF) and total powers in the lying position were higher compared with before and after. In normalized units, the increased HF in OT was even more prominent and clearly higher than in any control subject, and it was reversed in Rec. Resting heart rate was slightly reduced in OT and returned to baseline in Rec. Conclusions: The shift toward increased heart rate variability, particularly in the HF range, together with a reduced resting heart rate suggest a cardiac autonomic imbalance with extensive parasympathetic modulation in this athlete when overtrained.